Analisis Prospek Penerimaan Pajak Bumi dan Bangunan Di Kecamatan Asparaga Kabupaten Gorontalo - Samin Taliki (Universitas Gorontalo, 2018)
Gorontalo Province is still one of the newly developed areas that always expect the participation and support from various parties, both morally and spiritually in the form of facility improvement and human resource formation must be developed simultaneously, it is clear that this will encourage economic development for the society as a whole. This study aims to analyze the Prospect of Receipt of Land and Building Tax in District of Asparaga Gorontalo Regency. The main variables used are land tax and building. The analysis method used is Linear Trend analysis. The results showed that the Linear Trend is Y = 900343714,60 + 5006432,80 X which means the variable of the earth and building taxes have good prospects in the District Asparaga. And with the value of linear trend can be calculated the estimated value of land and building tax revenue for the period 2017-2021 in District Asparaga.Analisis Prospek Penerimaan Pajak Bumi dan Bangunan Di Kecamatan Asparaga Kabupaten Gorontalo